Genetic and physical studies of lambda transducing bacteriophage carrying the beta subunit gene of the Escherichia coli ribonucleic acid polymerase. - Ikeuchi, T (1975)
The prophage lambdac1857 was inserted into the bfe gene located near rif (the structural gene for the beta subunit of deoxyribonucleic acid [DNA]-dependent ribonucleic acid polymerase) on the Escherichia coli chromosome. Induced lysates (low-frequency transducing lysates) of such a lysogen contained defective lambda phage particles (lambdadrif+) that can specifically transduce the wild-type rif+ gene. Upon transduction into a recipient strain carrying recA, heterogenotes harboring both the wild-type and the mutant rif genes were isolated. Rec+ derivatives of these heterogenotes produce high-frequency transducing lysates that contain lambdadrif+ and normal active phages at a ratio of 1 to 2. The results of marker rescue experiments and of density determination with several transducing phages indicate that most of the late genes are deleted and replaced by a segment of the chromosomal DNA carrying the bfe-rif region. The length of the chromosomal segment seems to vary between approximately 0.5 and 0.6% of the total bacterial DNA among the three independently isolated lambdadrif+ phages. Electron microscopy of heteroduplex DNA consisting of one strand from lambdadrif+-6 and the other from lambdaimm-21 phages directly confirmed that most of the phage DNA of the "left arm" was replaced by the bacterial DNA. The heteroduplex study also demonstrated that the integration of prophage lambda into the bfe region occurred at the normal cross-over point within the phage attachment site.